Development of national physical activity recommendations in 18 EU member states: a comparison of methodologies and the use of evidence. Issue 4 (15th April 2021) - Tcymbal, Antonina; Gelius, Peter; Abu-Omar, Karim; Foster, Charlie; Whiting, Stephen; Mendes, Romeu; Titze, Sylvia; Dorner, Thomas Ernst; Halbwachs, Christian; Duclos, Martine; Toussaint, Jean-Francois; Wendel-Vos, Wanda; et al.
Abstract : Objectives: The aim of the study is to compare how member states of the European Union (EU) develop their national physical activity (PA) recommendations and to provide an overview of the methodologies they apply in doing so. Information was collected directly from the physical activity focal points of EU member states in 2018. Five countries were chosen for detailed case study analysis of development processes. Design: Cross-sectional survey. Participants: The representatives of the 28 EU member state governments to the EU physical activity Focal Point Network. Outcome measures: From national documents we extracted data on (1) the participants of the development process, (2) the different methods used during development, and (3) on which sources national PA recommendations were based. An additional survey for case study countries provided details on (1) anonymised information on the participants of development process, (2) methods employed and rationale for choosing them, (3) development process and timeline, and (4) main source documents used for recommendation development. Results: Eighteen national documents on PA recommendations contained information about development process. The results showed that countries used different approaches to develop national recommendations. The main strategies were (1) adoption of WHO 2010 recommendations or (2) a combination of analysis and adoption of other national and international recommendations and literature review. All of the five case study countries relied on review processes rather than directly adopting WHO recommendations. Conclusions: While there are arguments for the use of particular strategies for PA recommendation development, there is currently no evidence for the general superiority of a specific approach. Instead, our findings highlight the broad spectrum of potential development methods, resources utilisation and final recommendations design currently available to national governments. These results may be a source of inspiration for other countries currently planning the development or update of national PA recommendations.